1999
DOI: 10.1507/endocrj.46.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 22-Oxa-1,25-Dihydroxyvitamin D3 on Human Thyroid Cancer Cell Growth.

Abstract: Abstract.To examine whether synthetic vitamin D3 analog, 22-oxa-1,25(OH)2D3 (OCT) has an inhibitory effect on the growth of thyroid carcinoma, we tested the in vitro and in vivo effects of OCT on the growth of a welldifferentiated thyroid cancer cell line, NPA. OCT bound to its receptor at the same rate as 1,25(OH)2D3, and inhibited the proliferation of NPA cells in vitro in a dose-dependent manner, similar to that observed with 1,25(OH)2D3. Northern blot analysis showed that steady-state and fetal bovine seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…(Mathiasen et al 1993). The observation that 1,25(OH) 2 D 3 is able to regulate c-myc at the mRNA level is in accordance with the finding of a putative VDRE which has been reported in the human c-myc gene (Okano et al 1999).…”
Section: Mechanisms Associated With Inhibitory Effects Of Vitamin D Csupporting
confidence: 91%
“…(Mathiasen et al 1993). The observation that 1,25(OH) 2 D 3 is able to regulate c-myc at the mRNA level is in accordance with the finding of a putative VDRE which has been reported in the human c-myc gene (Okano et al 1999).…”
Section: Mechanisms Associated With Inhibitory Effects Of Vitamin D Csupporting
confidence: 91%
“…This hormone, in addition to its role in calcium homeostasis, has been recognized to play a role in the modulation of the proliferation and differentiation of several cell types (32). In vitro studies have demonstrated that vitamin D inhibits the proliferation of well-differentiated thyroid cancer cells in a dose-dependent manner (32,33). Therefore, as vitamin D is known to be protective in terms of cancer, insufficient levels of this hormone might be contributing to an increased cancer risk in individuals with excess weight.…”
mentioning
confidence: 99%
“…In terms of thyroid cancer, there have been several reports on the efficacy of vitamin D3 to inhibit proliferation and to induce re-differentiation of thyroid cancer cell lines in vitro [5,6]. Recently, similar results have also been reported in animal models and thus clinical trials are anticipated for further investigation on the therapeutic role of vitamin D3 in thyroid cancer [7].…”
Section: Discussionmentioning
confidence: 70%
“…In addition, vitamin D3 has been shown to inhibit the proliferation of various thyroid cancer cell lines in vitro [5,6]. Recently, Dackiw et al reported that calcitriol administration reduced the tumor burden and inhibited metastatic growth in an animal model of thyroid cancer [7].…”
mentioning
confidence: 99%